DAMPAK PENGGANDA KOMODITAS UNGGULAN TERHADAP PEREKONOMIAN NUSA TENGGARA TIMUR - Johny Agustinus Koylal; Stefanus M. Kuang (Politeknik Pertanian Negeri Kupang, 2022)
The agricultural sector is the leading sector in the economy of East Nusa Tenggara (NTT) in terms of its contribution to labor absorption. The large number of NTT people working in the agricultural sector indirectly shows that the economic development of the region also depends on contributions from the agricultural sector. The research aims to analyze the impact of the multiplier of superior commodities on the economy. The secondary data used in this study, namely the NTT Input-Output Table in 2020 obtained from the update of the NTT Input-Output Table in 2017 using the RAS method. The results showed that coffee commodities, livestock commodities, and poultry commodities and the results were categorized as superior commodities because they had a great impact on the formation of output as well as the welfare and absorption of labor in the NTT economy.Keywords: Commodities, Sector, Agriculture, Economy